5x-3(x-3)=4+5x-8

Simple and best practice solution for 5x-3(x-3)=4+5x-8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x-3(x-3)=4+5x-8 equation:


Simplifying
5x + -3(x + -3) = 4 + 5x + -8

Reorder the terms:
5x + -3(-3 + x) = 4 + 5x + -8
5x + (-3 * -3 + x * -3) = 4 + 5x + -8
5x + (9 + -3x) = 4 + 5x + -8

Reorder the terms:
9 + 5x + -3x = 4 + 5x + -8

Combine like terms: 5x + -3x = 2x
9 + 2x = 4 + 5x + -8

Reorder the terms:
9 + 2x = 4 + -8 + 5x

Combine like terms: 4 + -8 = -4
9 + 2x = -4 + 5x

Solving
9 + 2x = -4 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
9 + 2x + -5x = -4 + 5x + -5x

Combine like terms: 2x + -5x = -3x
9 + -3x = -4 + 5x + -5x

Combine like terms: 5x + -5x = 0
9 + -3x = -4 + 0
9 + -3x = -4

Add '-9' to each side of the equation.
9 + -9 + -3x = -4 + -9

Combine like terms: 9 + -9 = 0
0 + -3x = -4 + -9
-3x = -4 + -9

Combine like terms: -4 + -9 = -13
-3x = -13

Divide each side by '-3'.
x = 4.333333333

Simplifying
x = 4.333333333

See similar equations:

| 0.5x+6=17 | | -4(6x-7)=-24x-28 | | -12x-65=-7x | | 5-(2x+2)=-(-3x+5)-x | | 3(-2x+5)=9 | | 1x+.5y=6 | | 21=7y+7+(y+3) | | 7(-6x+1)=-329 | | X-2(x+3)=-2(x+1)-4 | | 2x+1+3x=30 | | x=a(a-b)+b(a+b) | | x=-3+13 | | 2x-3+19=17 | | 5x=63.25 | | [2x+3]=-5 | | 7(-1x+5)=-7 | | x^2-2+3x+8=180 | | -8y=48-4y | | 7.1x+4.4-2x-8.7= | | -7(2x+4)=-70 | | [8x+5]=21 | | 72-10x=12 | | -6x+2=3x-79 | | [4x-8]=20 | | x+4=-20-x | | 6x-3=-7x-133 | | 4-3x+2x=-18+2 | | 6=16-13d | | -140=4x-6(-x+10) | | 5y=-2x-15 | | 10x^2-42x+44=0 | | 5x+13=35+7x |

Equations solver categories